Outcomes of Open Versus Laparoscopic Surgery for Colorectal Cancer in the Emergency Setting - Barkha Kumari, Talha Aslam, Malik Muhammad Hamdan Tafheem, Muhammad Nauman Ashraf, Aftab Ahmad Baig, Sardar Muhammad Naseer Uddin (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The study aim is to do the comparison of oncological and short-term results of open and laparoscopic surgery for colorectal cancer in emergency setting. Study Design: This retrospective cohort research was held in the Department of Surgery, Civil Hospital, Karachi and Sheikh Zayed Medical College/ Hospital, Rahim Yar Khan for two-years duration from January 2020 to December 2021. Patients and Methods: after approval of this study and an informed consent agreement was signed by each participant. We performed an emergency analysis on 55 consecutive patients who received emergency open (n=40) or laparoscopic (n=15) resection for colorectal cancer. Results: The gender, age, BMI, American Society of Anesthesiologists (ASA) score, tumor location and prior abdominal surgery history were not significantly different between the laparoscopic and open groups. The T4 pathological tumors were more frequent in the open surgery group (50% vs. 13.3%; p=0.031) than in the laparoscopic group. The open surgery group also experienced high proportion of perforation (42.5% vs. 33.3%) and obstruction (47.5% vs. 26.7%) cases. In the laparoscopic group, bleeding or anemia were much common (33.3% vs. 7.5%; p=0.032). The laparoscopic group did not experience any open conversions. The open surgery group had a high pervasiveness of Hartmann’s surgery (35%), whereas the laparoscopic group had high pervasiveness of low anterior resection (26.7%; p=0.064). The complication ration at 30-days for laparoscopy (37.5%) and open surgery (33.3%) was comparable (p=0.900). Conclusions: In some individuals with colorectal cancer, emergency laparoscopic surgery has advantages in relation of short-term and oncologic outcomes. As a result, skilled laparoscopic surgeons may actively consider using laparoscopy in life-threatening situations. Keywords: Laparoscopy, colorectal cancer, and emergency.